Prevalence and factors associated with the occurrence of urinary incontinence during pregnancy - Ana Carolina Monteiro Santini; Elisiane Souza Santos; Luana Schneider Vianna; João Marcos Bernardes; Adriano Dias
Abstract Objectives: to determine the prevalence of urinary incontinence (UI) during pregnancy, to identify and quantify the factors associated with gestational UI. Methods: a cross-sectional study carried out with women admitted for deliveries in all maternity wards in the city of Botucatu (São Paulo). Data were collected through a structured questionnaire, based on the literature, containing questions about the occurrence of UI, its types, risk factors and moments when urinary losses occurred. Associations between UI and the predictive variables were analyzed with logistic regression models. Results: 950 women were interviewed, out of which 472 complained of urinary losses during pregnancy, resulting in a prevalence of 49.68% (CI95%= 46.51 - 52.86). The majority (61.8%) were classified as mixed UI. Among the covariates investigated, smoking (OR= 4.56), illicit drugs use (OR= 25.14), stimulant foods (OR= 1.84), constipation (OR=1.99), hypertensive disorders during gestation (OR= 3.23), gestational diabetes mellitus (OR= 2.89), parity (OR= 1.52) and previous caesarean sections (OR= 2.56) increased the chance of urinary losses during pregnancy. Conclusions: there was a high prevalence of UI during pregnancy. This condition was strongly associated with lifestyle habits and gestational morbidities. Finally, it is worth high-lighting the fact that delivery via caesarean section increased the chance of UI in subsequent pregnancies.